2018
DOI: 10.1051/matecconf/201815005084
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Psychological Well-Being among Hearing-Impaired: Does it Relates?

Abstract: Abstract. This paper explores the relationship between emotional intelligence and psychological wellbeing among hearing-impaired students. Emotional intelligence consists of five dimensions namely intrapersonal, interpersonal, adaptability, stress management and general mood. A total of 130 hearingimpaired students were chosen as participants via simple random sampling at four polytechnics in Malaysia. The Bar-On Emotional Quotient: Short (EQ-i: S) and Ryff's Psychological Well-Being instruments were utilised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Conversely, students from inclusive settings outperformed their segregated counterparts in Empathy alone (Mean=3.16, SD=0.49), with a t-value of 2.06 (p=0.039). The overall EI, however, was notably lower for the inclusive group (Mean=2.61, SD=0.49) compared to the segregated group (Mean=2.81, SD=0.47) (16)(17)(18)(19). These findings parallel those from related research, where sensory-impaired students exhibited varied EI levels, with empathy often scoring higher in contrast to other EI components (17,18).…”
Section: Figure 1 Comparative Emotional Study Characteristicssupporting
confidence: 78%
See 1 more Smart Citation
“…Conversely, students from inclusive settings outperformed their segregated counterparts in Empathy alone (Mean=3.16, SD=0.49), with a t-value of 2.06 (p=0.039). The overall EI, however, was notably lower for the inclusive group (Mean=2.61, SD=0.49) compared to the segregated group (Mean=2.81, SD=0.47) (16)(17)(18)(19). These findings parallel those from related research, where sensory-impaired students exhibited varied EI levels, with empathy often scoring higher in contrast to other EI components (17,18).…”
Section: Figure 1 Comparative Emotional Study Characteristicssupporting
confidence: 78%
“…In the segregated environment, students demonstrated superior scores across most EI dimensions, notably in Interpersonal Skill (Mean=3.10, SD=0.63), Self-Regard (Mean=2.69, SD=0.63), Assertiveness (Mean=2.75, SD=0.60), and Emotional Self-Awareness (Mean=2.71, SD=0.56) with p-values all below .005, indicating a robust statistical significance (16)(17)(18)(19). Conversely, students from inclusive settings outperformed their segregated counterparts in Empathy alone (Mean=3.16, SD=0.49), with a t-value of 2.06 (p=0.039).…”
Section: Figure 1 Comparative Emotional Study Characteristicsmentioning
confidence: 96%
“…Therefore, we assumed that EI could not only reduce the negative emotions felt because of the fear of terrorism and its related stress but also aid in the maintenance of positive emotions and psychological well-being despite the negative circumstances [ 41 , 42 ]. The concepts of EI, psychological well-being, and health have attracted the attention of numerous studies in recent years [ 43 , 44 , 45 , 46 , 47 , 48 ]. Lau and Wu [ 49 ] stated that EI is a vital component of ‘social maturity’ that enhances the psychological health of adolescents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have demonstrated a positive association between EQ and PWB (Guerra-Bustamante et al, 2019;Malinauskas & Malinauskiene, 2020;Marzuki et al, 2018).…”
Section: Construct Relationshipsmentioning
confidence: 99%